Analysis of amphetamine‐type substances and piperazine analogues using desorption electrospray ionisation mass spectrometry. (13th February 2014) - Stojanovska, Natasha; Kelly, Tamsin; Tahtouh, Mark; Beavis, Alison; Fu, Shanlin
<x xml:space="preserve">Abstract</x> RATIONALE Although amphetamine‐type substances (ATS) have been investigated extensively in recent years, scarce data is available on screening tests for piperazine analogues. The need for a universal technique capable of detecting an extensive range of drug compounds becomes increasingly important with the continued emergence of novel drug analogues. METHODS Desorption electrospray ionisation mass spectrometry (DESI‐MS) is a technique that allows examination of compounds in drug materials directly from ambient surfaces. In this study, DESI‐MS was utilised in the analysis of ATS including amphetamine (AP), methylamphetamine (MA), 3, 4‐methylenedioxymethylamphetamine (MDMA), N, N‐dimethylamphetamine (DMA), 4‐methoxyamphetamine (PMA) and 4‐methoxymethylamphetamine (PMMA), and piperazine analogues including 1‐benzylpiperazine (BZP), 1‐[3‐(trifluoromethyl)phenyl]piperazine (TFMPP), 1‐(3‐chlorophenyl)piperazine (mCPP) and 1‐(4‐methoxyphenyl)piperazine (MeOPP). Semi‐porous polytetrafluoroethylene (PTFE or Teflon) sheets welled with a 3 mm hole punch were used to contain the 2 μL liquid sample (spot size 7 mm2). RESULTS The limits of detection (LODs) of these compounds using DESI‐MS were determined to be in the range 0.02–2.80 µg/mm2. The intra‐day and inter‐day precision of the technique were <25% and <33%, respectively. DESI‐MS was successful in determining the compound of interest and reaction by‐products and impurities in the samples tested (such as 1, 4‐dibenzylpiperazine in BZP samples) with the exception of those present in trace amounts. The effects of common adulterants on the detectability of MA were evaluated. The addition of magnesium stearate to MA significantly enhanced the signal response. CONCLUSIONS This work has demonstrated the applicability of DESI‐MS in the screening and profiling of MDMA, PMMA, BZP, TFMPP, mCPP, MeOPP as well as other complex mixtures. Copyright © 2014 John Wiley & Sons, Ltd.